Innovation as A Driver of SMEs Sustainability: A Systematic Review of the Literature - Latifannisa, Nuri; Yunia Wardi; Marwan (BASKARA : Journal of Business and Entrepreneurship, 2025)
One interesting area of research is innovation for the sustainability of Small and Medium Enterprises (SMEs), which has increasingly attracted economists' attention in recent years. This paper is a literature review of several articles on the application of innovation to encourage SME sustainability. This paper aims to ensure that technological, process, and production innovation are integrated ways to drive SME sustainability and are most widely used in the literature, especially about SME sustainability. Based on a comprehensive review of innovation variables with systematic literature review methods, the search yielded 25 articles from journal publications indexed in ScienceDirect. The results concluded that product innovation could create significant added value and open up new market opportunities while marketing innovation and business models can increase customer reach and adaptability of SMEs to a dynamic business environment. Product innovation, marketing, and business models can be applied to encourage SMEs' sustainability to encourage SMEs' sustainability. Government policy support, access to financing, and strategic partnerships are critical factors for the success of this innovation initiative, which overall improves the competitiveness and viability of SMEs.